Harnessing the Power of Storytelling and Storylistening: Fostering Challenging Conversations in Coastal Communities - Parker, Holly (Maine Policy Review, 2023)
As sustainability practitioners we often spend our time in vibrant echo chambers. We’re invigorated by debates about how to support just and sustainable communities and environments. But what happens outside that echo chamber? What happens when we meet a neighbor, a colleague or a decisionmaker who doesn’t share our urgency for action? Do we go it alone as we seek to make change? Or do we need to build new, unexpected partnerships? In a time when technology and political and social divisiveness make it easy to dismiss the other, it is vital that we build pathways to understanding opposing points of view and better communicating our own. Storytelling and storylistening are vital tools to breaking down perceived barriers to collaboration and cooperation. Sustainability practitioners should challenge ourselves to approach those of opposing views with empathy.
Keywords: policy; sustainability; qualitative research; communications; rural community engagement